KONSEP PENDIDIKAN MULTIKULTURAL, STUDI PERBANDINGAN PRAKTIK MULTIKULTURAL DI BERBAGAI NEGARA - Nurjannah; Karyawati, Lilis; Aziz, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze in depth the basic concept of multicultural education and compare its models and applications in different countries. Multicultural education is understood as a conscious effort to develop the potential of students to respect cultural, ethnic, and religious diversity, with the aim of realizing social justice and reducing prejudice. The theoretical framework of this research refers to the dimensions proposed by James Banks, including content integration, knowledge construction, prejudice reduction, equality pedagogy, and cultural empowerment and school structure. Through a comparative literature review, the study examined the practice of multicultural education in the United States and Canada. The results of the analysis show that the United States is focused on eliminating racial discrimination rooted in the Civil Rights Movement, with an emphasis on curriculum reform and teacher competency improvement. Meanwhile, Canada, which has made multiculturalism a national policy, is developing a more systematic approach to building inclusive cultures through second-language programs and the preservation of the mother tongue for immigrants. These differences indicate that the success of the implementation of multicultural education is greatly influenced by the historical context, policy support, and level of community diversity